Eternal life: a new vision; beyond religion, beyond theism, beyond heaven and hell - Spong, John Shelby (Harper One, 2009)
Setting the stage : a necessary personal word -- Life is accidental -- All life is deeply linked -- Life is mortal -- The lure of religion -- Life's dominant drive : survival -- Religion's role in the fear of death -- The faces of religion -- The tools of religious manipulation -- Ridding religion of both heaven and hell -- Putting away childish things : the death of religion -- The shift of the religious paradigm -- Who am i? What is God? -- The approach of the mystics -- Resurrection : a symbol and a reality -- Hiding, thinking, being -- I believe in life beyond death -- Epilogue : defining the choice to die